Pengaruh Sistem Pengendalian Manajemen Terhadap Kinerja perusahaan pada Pembelajaran Organisasi Dan Inovasi Sebagai Variabel Intervening (Studi Kasus Badan Pengkreditan Rakyat Kota Pekan Baru) - Fadillah, Aditya; Nafis, Fadly Abdillah; Aisyah, Siti (Jurnal Manajemen Akuntansi (JUMSI), 2022)
According to Porporato (2006), management control systems are required to exist in companies and other institutions as a very important tool in corporate organizations and institutions in order to create performance from existing human resources to work optimally and overall within a company. The research method used was census sampling, with a small population of less than 30 people who were also sampled in this study. The results of the research are there are several divisions in the management control system, namely the belief system, boundary system, diagnostic control system, and control system that greatly influences the performance of human resources in the company. And a management control system that does not affect the company's performance through innovation but the company's performance through organizational learning and innovation.